Digitalisasi Budaya Wayang Pothehi Melalui Film Dokumenter pada Komunitas FU HE AN - Ambarastuti, Retno Dewi; Fatimah, Emma Rahmawati; Paramita, Ni Made Savitri; Andayani, Santi; Wijaya, Clarinta Gaby; Prakoso, Nando Petra Setyo; Ramadhani, Muhammad Aus; Ardhiansyah, Muhammad Farel; Widyanto, Muhammad Rizal (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2025)
Potehi puppetry is an art performance that uses puppets from South China, which came to Indonesia in the 16th and 17th centuries. The development of these puppet shows experienced ups and downs, especially the prohibition of everything with Chinese nuances, in 1967 and improved in 2000. The preservation and continuity of potehi puppets are also carried out by the Fu He An community, Gudo, Jombang, led by Toni Harsono. Toni Harsono's motivation to develop this community stems from his concern about the condition of many damaged potehi puppets, the scarcity of authentic potehi puppets, and his desire to re-modify them so they can be preserved for the future. Toni Harsono's efforts have been welcomed by academics from within and outside the country, who have conducted various studies on potehi puppets. The public has also carried out the preservation and sustainability of potehi puppets through social media. However, the Fu He An community still needs to work on accessing information and understanding cultural digitization, especially in the context of making documentary films. Therefore, this community service activity aims to create a series of documentary films with the initial theme of the history of the making and character formation of the Jombang; Gudo potehi puppets, and make a Instagram account and website Wayang Potehi, Gudo. Keywords: cultural digitalization, sustainability, preservation, wayang potehi